INCLUSIVE REHABILITATION AND SOCIAL TOURISM AS A SOCIAL SERVICE FOR PEOPLE WITH DISABILITIES: THE EXPERIENCE OF IMPLEMENTATION IN THE TOWN OF UMAN (UKRAINE) - Kucher, Galina M.; Kravchenko, Oksana (Revista Inclusiones, 2021)
In the study, we consider the fact that inclusive rehabilitation and social tourism is a type of tourism that serves an innovative creative social service for people with disabilities, which involves medical, psychological, pedagogical, physical, professional, labor, sports and social measures, taking into account accessibility for everybody, through adapting the infrastructure of tourist centers and tourist attractions. The purpose of the study is to cover the practical experience of implementing inclusive rehabilitation and social tourism as a social service in the conditions of a territorial community (Uman). In order to assess the effectiveness of community-based inclusive social and rehabilitation tourism measures implemented during 2016–2018, a survey was conducted among social service recipients at the end of 2018, in which 25% of the users (254 people) took part. Such methods of evaluation are used: questionnaires, questionnaires filled in by participants in order to receive feedback on social services organization and provision. Indicators such as targeting and individual approach, effectiveness, timeliness, accessibility and openness, respect for the dignity of the social services recipient and professionalism were used in conducting an internal assessment of the social service provision quality.